(untitled) - Karthik Marpalli Vasudeva (Asian Journal of Medical Radiological Research, 2019)
Background: Hepatobiliary surgery requires a detailed preoperative evaluation of vascular anatomy through a noninvasive modality. The purpose of our study was to determine the anatomical variation in the hepatic arteries and classify them according to Michels classification in patients who underwent abdominal angiography for various reasons. Subjects and Methods: This was a prospective study done in a tertiary care hospital in northern India which included 500 consecutive patients undergoing triple-phase abdomen CT for various abdominal indications. Plain CT followed by triple-phase CT angiography of the abdomen was performed. The origin and branches of the hepatic artery were examined in detail and classified according to Michels classification. The unnamed variants and other abnormal findings were mentioned separately.Results:Out of 500 patients, there were 268 males and 234 females. Three hundred and eleven out of the 500 patients (62.2%) had the classic arterial anatomy identified at CT angiography.  The most common variant identified was Michels type V (9%). The second most common variant identified was Michels type III (6.4%). Ninety-seven (19.4%) had a single arterial aberration, and 25 patients (5%) showed more than one arterial variant. There was a trifurcation pattern identified in 20 patients (4%). Different combinations of accessory and replaced hepatic arteries were identified in 26 patients (5.2%).Both Males and females had type 5 as the most common variation in our study followed by type 3.Conclusion: Our study shows a high prevalence of the hepatic arterial variation in our population (37.8 %).